Aspek Hukum dalam Bisnis - Firmansyah, Mohammad Aditiya; Ramadhan, Rehan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The legal aspects of business are essential elements that ensure continuity and fairness in economic activities. Every business activity, whether small or large scale, is governed by legal rules that regulate the rights and obligations of business actors. This study aims to identify and analyze various legal aspects inherent in the business world, such as contract law, corporate law, consumer protection law, as well as taxation and business licensing regulations. A normative juridical approach is used to understand the relevance and implementation of laws and regulations in business practices in Indonesia. The findings indicate that understanding and complying with legal aspects can create an orderly, transparent, and competitive business environment. Furthermore, the existence of clear and firm legal regulations also enhances investor confidence and provides protection for both business actors and consumers.